2017
DOI: 10.1085/jgp.201711788
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic cooperativity of cosubstrate binding and cation selectivity of Salmonella typhimurium MelB

Abstract: The melibiose symporter MelB couples melibiose transport to that of cations such as Na+. Hariharan and Guan show that the binding of Na+ and melibiose is thermodynamically cooperative and that Na+ coupling is based on ion concentrations and competitive binding, but not ion selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(77 citation statements)
references
References 47 publications
7
70
0
Order By: Relevance
“…We also note, however, that the chemical makeup and structure of the N-lobe Na + -binding site indicates that it is weakly Na + -specific against H + ; indeed, Na + coupling in MATEs likely results from the fact that Na + is in large excess over H + in most settings. This phenomenon is not uncommon; inherently H +selective sites that mediate Na + -driven activity in physiologically realistic conditions have been reported for other membrane enzymes and transporters, such as rotary ATP synthases (27,41) and amino acid and sugar symporters (42,43). This promiscuity between Na + and H + , modulated by the specific protein environment, would explain the observation of H + -driven function or other pH-dependent effects in MATEs featuring the Na + -binding motif described here.…”
Section: Discussionsupporting
confidence: 65%
“…We also note, however, that the chemical makeup and structure of the N-lobe Na + -binding site indicates that it is weakly Na + -specific against H + ; indeed, Na + coupling in MATEs likely results from the fact that Na + is in large excess over H + in most settings. This phenomenon is not uncommon; inherently H +selective sites that mediate Na + -driven activity in physiologically realistic conditions have been reported for other membrane enzymes and transporters, such as rotary ATP synthases (27,41) and amino acid and sugar symporters (42,43). This promiscuity between Na + and H + , modulated by the specific protein environment, would explain the observation of H + -driven function or other pH-dependent effects in MATEs featuring the Na + -binding motif described here.…”
Section: Discussionsupporting
confidence: 65%
“…Channel's SF. The apparent K + -binding affinity for the KcsA's SF under equilibrium conditions was measured by isothermal titration calorimetry (ITC), as has been done before for measuring the apparent cation-binding affinity to membrane transporters (31,32). This measurement is considered an apparent ion-binding affinity because it was performed in the presence of 100-mM Na + ions, which could compete against K + ions for the SF's ion-binding sites.…”
Section: Ion-binding Properties Of the 24-ion-bound Configuration Ofmentioning
confidence: 99%
“…S1, blue); Residues Tyr120, Asp124, and Lys377 (Fig. S1, purple) may be shared by both binding sites [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…2A, left). Although human TMEM180 has only 19% sequence identity with stMelB, comparison of the crystal structure of stMelB with the homology model of human TMEM180 revealed that five putative cation-binding residues (Asn63, Asn66, Asp67, Thr139, and Asp142) in the homology model were located in positions similar to those of five cation-binding residues of stMelB (Asp55, Asn58, Asp59, Thr121, and Asp124) [24,25] ( Fig. 2A,B).…”
Section: Homology Modeling Of Human Tmem180mentioning
confidence: 99%